Evolving role of tumor antigens for future melanoma therapies. (June 2014) - Andrews, Miles C; Woods, Katherine; Cebon, Jonathan; Behren, Andreas
ABSTRACT: : Human tumor rejection antigens recognized by T lymphocytes were first defined in the early 1990s and the identification of shared tumor-restricted antigens sparked hopes for the development of a therapeutic vaccination to treat cancer, including melanoma. Despite decades of intense preclinical and clinical research, the success of anticancer vaccines based on these antigens has been limited. While melanoma is a highly immunogenic tumor, the ability to prime immunity with vaccines has not generally translated into objective disease regression. However, with the development of small molecules targeting oncogenic proteins, such as V600-mutated BRAF, and immune checkpoint inhibitors with demonstrable long-lasting clinical benefit, new opportunities for antigen-targeted directed therapies are emerging.